Effects of Clostridium difficile toxin A and toxin B on phospholipase D activation in human promyelocytic leukemic HL60 cells. - Ohguchi, K (1996)
The possible involvement of Rho family GTP-binding proteins in the regulation of phospholipase D (PLD) activity has recently been demonstrated. In the present study, to further examine the role of Rho family proteins in PLD activation of human promyelocytic leukemic HL60 cells, we used toxin A and toxin B from the anaerobic bacterium Clostridium difficile, which was shown to glucosylate Rho family proteins and inhibit their interaction with effectors. Pretreatment of [3H]oleic acid-labeled HL60 cell lysates with either one of the toxins resulted in a remarkable inhibition of membrane PLD activity stimulated by guanosine 5'-O-(3-thiotriphosphate) (GTPgammaS). The magnitude of inhibition of PLD activity was correlated well with the extent of toxin A- or B-induced glucosylation of 22-kDa RhoA in HL60 cells, toxin B being more effective than toxin A. GTPgammaS-stimulated PLD activation measured with the exogenous substrate containing phosphatidylinositol 4,5-bisphosphate was also inhibited by toxin B. Toxin B had no effect on GTP-gammaS-induced translocation of RhoA from cytosol to membranes. Furthermore, the toxin B pretreatment also suppressed PLD activation induced by 4beta-phorbol 12-myristate 13-acetate in HL60 cell lysates. Thus, it was indicated that Rho family proteins play a key role in GTPgammaS- and 40-phorbol 12-myristate 13-acetate-induced PLD activity in HL60 cells. In addition, the results obtained here indicate that C. difficile toxins are a useful tool for researching the regulation of the Rho family protein-mediated PLD activation and also provide a clue toward understanding the pathogenic background of pseudomembranous colitis from the viewpoint of signal transduction.